2019
DOI: 10.1155/2019/9140179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Voltage Electric Field Process Parameters on the Water-Holding Capacity of Frozen Beef during Thawing Process

Abstract: In order to investigate the thawing time and water-holding capacity under high-voltage electric field (HVEF), we studied the thawing experiments of frozen beef in a multiple needles-to-plate electrode system. The electric field, thawing characteristics, and quality parameters during the thawing process were measured. The results showed that compared with the control, the thawing time of beef under HVEF was significantly shortened, the thawing rate increased significantly, the drip loss decreased, and the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…e needle-plate corona discharge device was widely used in promoting seed germination [20,21], drying [22,23], thawing [24], and other aspects. In order to improve the concentration of plasma active particles and highlight the effect of electric field on water, the DBD structure and the traditional needle array-plate corona discharge structure were combined, and a needle array-plate DBD device was used.…”
Section: Introductionmentioning
confidence: 99%
“…e needle-plate corona discharge device was widely used in promoting seed germination [20,21], drying [22,23], thawing [24], and other aspects. In order to improve the concentration of plasma active particles and highlight the effect of electric field on water, the DBD structure and the traditional needle array-plate corona discharge structure were combined, and a needle array-plate DBD device was used.…”
Section: Introductionmentioning
confidence: 99%
“…As detailed in the aforementioned sections, in the nonuniform electric field generated by the plate electrode, the free electrons are accelerated under the action of the electric field force to form corona wind (Goodenough et al., 2007; Dalvi‐Isfahan et al., 2016) and then collide with the uncharged particles in the electric field and generate turbulence and vortex, thereby producing a good heat transfer effect (He et al., 2016; H. Huang et al., 2020; Li, Jia, Zhang, Li, et al., 2017). Numerous studies have shown that the effect and energy consumption of electric field thawing are related to the voltage, electrode spacing, and distance between adjacent needles (Bai et al., 2011; Y. M. Zhang et al., 2019).…”
Section: Key Factors Of Thawing Technologies Affecting Muscle Foodsmentioning
confidence: 99%
“…Therefore, the increase in the heat transfer coefficient resulted in faster thawing. In addition, the rise of thawing voltage also had an excellent inhibitory effect on the drip loss and centrifugal loss of frozen muscle foods (Y. M. Zhang et al., 2019). At a constant thawing voltage, the thawing rate was inversely proportional to the electrode spacing (Y. M. Zhang et al., 2019), possibly because moving ionized air has a greater collision frequency than nonionized air at a smaller electrode spacing, which increases the heat transfer coefficient of the contact surface (He et al., 2013).…”
Section: Key Factors Of Thawing Technologies Affecting Muscle Foodsmentioning
confidence: 99%
See 2 more Smart Citations